Effects of Ficus carica L. polysaccharide on the intestinal immune function and microbiota of broilers - Lu, Yabin; Maimaiti, Sajidaimu; Qin, Zhanke; Cheng, Xinke; Li, Jianlong; Zhou, Chuang; Xiao, Ying; Abula, Saifuding; Kuang, Ling; Mai, Zhanhai (Frontiers in Immunology, 2025)
IntroductionFicus carica L. polysaccharides (FLPs) are groups of biologically active compounds extracted from Ficus carica L.MethodsIn this study, we analyzed the structure of FLPs, predicted their immune enhancement pathway, and detected the impact of FLPs on the growth performance, immune function, and intestinal microflora of broiler chickens.ResultsThe results showed that FLPs are comprised of monosaccharides including rhamnose, arabinose, mannose, glucose, and galactose. Feeding with FLPs significantly promoted the growth performance, slaughtering performance, and immune organs index of chickens compared to the control group (p < 0.05). Moreover, the FLP-h and FLP-m groups had increased levels of sIgA, IgG, IL-4, IL-5, IL-12, and IFN-g; improved immunity and barrier function; and a higher percentage of spleen CD4+ and CD8+ T cell differentiation compared to the control group (p < 0.05). Additionally, the FLP-h group had increased levels of various SCFAs, and increased beneficial bacteria such as Firmicutes at the phylum level and Faecalibacterium, Blautia, Phascolarctobacterium, and Alistipes at the genus level. The results of network pharmacology and KEGG pathway prediction indicate that FLPs may change the structure and metabolism of intestinal microbiota by enhancing carbon fixation pathways in prokaryotes, and promote intestinal immune barrier function through the joint action of bisphenol degradation, retinol metabolism, NODlike signaling pathways, toll-like receptor signaling pathways, and the MAPK signaling pathway. DiscussionThese results suggest that FLP-h supplementation effectively promotes growth performance and enhances the intestinal mucosal immune barrier function in chickens.